EFFECT OF DIABETES MELLITUS TYPE II ON ACTIVATED PARTIAL THROMBOPLASTIN TIME AND PROTHROMBIN TIME - Elhassade, Amal S (International Journal of Clinical and Biomedical Research, 2016)
Diabetes mellitus contributes for initiation and progression of micro vascular and macro vascular complications. Complication includes coagulation impairment however Shortened activated partial thromboplastin time (aPTT) values may reflect hypercoaguable state, which is associated with increased thrombotic risk and adverse cardiovascular events. Objective: The present study was conducted to study the aPTT and PT levels in patients with diabetes mellitus type II. Material and method: A sample of 50 persons were selected, 30 patients suffering from DM as type II from Al-wahda teaching hospital, Derna-Libya. At the same time a group of 20 randomly selected healthy adults to participate in the study as control group. Result: The mean value of APTT in T2DM individuals was significant lower (28.95 ±7.54) seconds as compare with control, (34.12±2.82) seconds (P = 0.06). Â The mean value of prothrombin time (PT) among T2DM individuals was (14.04 ±2.96) seconds and the mean value of PT among healthy individuals was (13.5 ± 1.54) seconds. There was no significant difference in PT of T2DM individuals P < 0.05. Conclusion: From this study, it may be concluded that shorted APTT confirms that T2DM is a hyper-coagulable state due to which there is increased risk of thrombotic events.